2006
DOI: 10.1002/oti.208
|View full text |Cite
|
Sign up to set email alerts
|

Promoting autonomy of the client with persistent mental illness: A challenge for occupational therapists from The Netherlands, Germany and Belgium

Abstract: The aim of this study was to determine how occupational therapists from The Netherlands, Germany and Belgium promote the autonomy of clients with persistent mental illness. Sixty occupational therapists working in psychosocial mental health completed two semi-structured questionnaires. Data were analysed by applying the constant comparative method. The results of the study show the importance of handling motivation in relation to personal autonomy and the different strategies occupational therapists use in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 10 publications
0
12
0
3
Order By: Relevance
“…This is a very important issue in health care because enhancing patients' personal autonomy will empower and help them to make meaningful decisions. [4] However, it must be taken into consideration that in Muslim countries, families play a major role in medical decisions. The patient must listen to the opinion of close family members about the treatment he or she is going to accept.…”
Section: Introductionmentioning
confidence: 99%
“…This is a very important issue in health care because enhancing patients' personal autonomy will empower and help them to make meaningful decisions. [4] However, it must be taken into consideration that in Muslim countries, families play a major role in medical decisions. The patient must listen to the opinion of close family members about the treatment he or she is going to accept.…”
Section: Introductionmentioning
confidence: 99%
“…The Canadian Occupational Performance Measure (COPM) is an individualised client-oriented measure to assess the evolution of self-perception of skills in patients across time [34,35]. The COPM was, for example, used by Trombly and co-workers [36] to investigate the association between participation in goal-specific outpatient occupational therapy and improvement in self-identified goals in adults with acquired brain injury.…”
Section: Methodsmentioning
confidence: 99%
“…Granse et al (2006) labelled the liberal-individualist view of autonomy as primarily a Western concept that does not recognise the individual as part of a societal network. Therefore, the notion of interdependence has gained acceptance, as human beings are interdependent within a large network of people, systems and services (Corbett 1996).…”
Section: The Difficulties With Defining Independencementioning
confidence: 98%
“…Granse et al (2006) found that occupational therapists made choices depending on their own concept of autonomy. In practice, beyond personal interpretation components, a therapist's practice techniques can influence estimations of independence.…”
Section: Data Synthesis From Clinical Themesmentioning
confidence: 99%